2012
DOI: 10.1248/bpb.b12-00197
|View full text |Cite
|
Sign up to set email alerts
|

Interruption of Hepatocyte Growth Factor Signaling Augmented Oridonin-Induced Death in Human Non-small Cell Lung Cancer A549 Cells <i>via</i> c-Met-Nuclear Factor-κB-Cyclooxygenase-2 and c-Met-Bcl-2-Caspase-3 Pathways

Abstract: The aim of this study was to elucidate the molecular mechanisms mediating hepatocyte growth factor (HGF)-induced protection against oridonin-induced apoptosis in A549 cells. Oridonin induced decrease in Bcl-2/Bax ratio and activation of caspase-3, while these processes were reversed by HGF, suggesting that HGF played an anti-apoptotic role in oridonin-induced A549 cell death. HGF-induced protective effect was partially attributed to the activation of nuclear factor (NF)-κB and cyclooxygenase 2 (COX-2), since t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 51 publications
(54 reference statements)
0
13
0
Order By: Relevance
“…Given the close relationship between vascular density and cell survival, the VEGF-mediated angiogenesis might contribute towards improved engraftment of HGF-transfected cells in failing heart, which could ameliorate the heart function post-MI. Moreover, HGF-induced cell survival was associated with the c-Met-Bcl-2-caspase-3 signaling pathways [39]. We found that the levels of Bcl-2 significantly increased in the myocardial tissue after cell transplantation.…”
Section: Discussionmentioning
confidence: 97%
“…Given the close relationship between vascular density and cell survival, the VEGF-mediated angiogenesis might contribute towards improved engraftment of HGF-transfected cells in failing heart, which could ameliorate the heart function post-MI. Moreover, HGF-induced cell survival was associated with the c-Met-Bcl-2-caspase-3 signaling pathways [39]. We found that the levels of Bcl-2 significantly increased in the myocardial tissue after cell transplantation.…”
Section: Discussionmentioning
confidence: 97%
“…During apoptosis, the permeability of the mitochondrial membrane increased, leading to a loss of membrane potential and release of cytochrome c into the cytosol, which binds to apoptotic protease activating factor-1 (Apaf-1). 17 The Bcl-2 and Bcl-xL proteins have been identified as antiapoptotic proteins, which bind to the outer membrane of the mitochondrion and prevent the release of cytochrome c . 18 The proapoptotic members of this family, Bax and Bak, are responsible for permeabilizing the membrane under stress and promoting the release of cytochrome c from the mitochondria.…”
Section: Resultsmentioning
confidence: 99%
“…A number of previous studies have also demonstrated that HGF exerted an anti-apoptotic effect through the proapoptotic caspase-3 signaling pathway in various cells. 34,35) It has been reported that PTX can significantly decrease caspase-3 activities and reduce apoptosis to a significant extent in rat pups with hypoxic-ischemic encephalopathy. 36) Collectively, our data suggest that PTX prevents the activation of myocardial apoptosis induced by ADR, and the anti-apoptotic effect of PTX is probably mediated through cellular signaling of the HGF pathways.…”
Section: Discussionmentioning
confidence: 99%